2020
DOI: 10.1186/s12879-020-05306-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in clinical and CT characteristics of COVID-19 cases with different exposure histories: a retrospective study

Abstract: Background: To assess the dynamic changes in clinical and CT characteristics of COVID-19 patients with different epidemiology histories. Methods: Fifty-three discharged COVID-19 patients were enrolled at Beijing YouAn Hospital, Capital Medical University, between January 21 and March 10, 2020. Spearman correlation analysis was performed between CT scores and laboratory indicators. Patients were divided into the Wuhan group (lived in or with travel to Wuhan, numbering 30 cases) and non-Wuhan group (close contac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…Известно, что улучшение по КТ может несколько отставать от клиники и, возможно, у нас был недостаточный срок наблюдения для получения более существенной динамики [31,32]. Более того, единой точки зрения о времени полной нормализации КТ-картины легких при «ковидной» пневмонии не существует, но имеются предположения, что это происходит не ранее, чем через четыре недели после выписки из стационара [33]. Имелась не очень тесная, но статистически значимая корреляция между динамикой поражения легких по КТ и показателем выраженности воспаления отношения лимфоцитов / СРБ (r= -0,37, p=0,025).…”
Section: редакционные статьи §unclassified
“…Известно, что улучшение по КТ может несколько отставать от клиники и, возможно, у нас был недостаточный срок наблюдения для получения более существенной динамики [31,32]. Более того, единой точки зрения о времени полной нормализации КТ-картины легких при «ковидной» пневмонии не существует, но имеются предположения, что это происходит не ранее, чем через четыре недели после выписки из стационара [33]. Имелась не очень тесная, но статистически значимая корреляция между динамикой поражения легких по КТ и показателем выраженности воспаления отношения лимфоцитов / СРБ (r= -0,37, p=0,025).…”
Section: редакционные статьи §unclassified
“…The most COVID-19 cases (> 70%) show ground glass opacities with consolidation and interstitial and/or interlobular septal thickening in Thorax CT (13). COVID-19 predominant CT findings are bilateral, peripheral and basal predominant ground-glass opacity, consolidation, or both (14).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ruili LI from Beijing also correlated various laboratory parameters including AGR and compared with CT severity index and found significant correlation of change in AGR with CT severity [15]. This study tries to find out that which one is more accurate predictor marker of severity of COVID-19 infection and result showed that NLR as compared to AGR is better predictor marker in terms of sensitivity (92.86 vs.85.71), specificity (97.87 vs. 93.62), positive predictive value (96.3 vs. 88.9) and negative predictive value (95.83 vs. 91.67).…”
Section: Discussionmentioning
confidence: 99%